Novel immune modulators used in hematology: impact on NK cells - Krieg, Stephanie; Ullrich, Evelyn (Frontiers in Immunology, 2013)
There is a wide range of important pharmaceuticals used in treatment of cancer. Besides their known effects on tumor cells, there is growing evidence for modulation of the immune system. Immunomodulating drugs (IMID®s) play an important role in the treatment of patients with multiple myeloma or myelodysplastic syndrome and have already demonstrated antitumor, anti-angiogenic and immunostimulating effects, in particular on natural killer (NK) cells. Tyrosine kinase inhibitors (TKIs) are directly targeting different kinases and are known to regulate effector NK cells and expression of NKG2D ligands on tumor cells. Demethylating agents, histone deacetylases and proteasome inhibitors interfere with the epigenetic regulation and protein degradation of malignant cells. There are first hints that these drugs also sensitize tumor cells to chemotherapy, radiation and NK cell-mediated cytotoxicity by enhanced expression of TRAIL and NKG2D ligands. However, these pharmaceuticals may also impair NK cell function in a dose- and time-dependent manner. In summary, this review provides an update on the effects of different novel molecules on the immune system focussing NK cells.